Perceiving Space and Optical Cues via a Visuo-Tactile Sensory Substitution System: A Methodological Approach for Training of Blind Subjects for Navigation. (May 2013) - Segond, Hervé; Weiss, Déborah; Kawalec, Magdalena; Sampaio, Eliana
A methodological approach to perceptual learning was used to allow both early blind subjects (experimental group) and blindfolded sighted subjects (control group) to experience optical information and spatial phenomena, on the basis of visuo-tactile information transmitted by a 64-taxel pneumatic sensory substitution device. The learning process allowed the subjects to develop abilities in spatial localisation, shape recognition (with generalisation to different points of view), and monocular depth cue interpretation. During the training phase, early blind people initially experienced more difficulties than blindfolded sighted subjects (having previous perceptual experience of perspective) with interpreting and using monocular depth cues. The amelioration of the performance for all blind subjects during training sessions and the quite similar level of performance reached by two groups in the final navigation tasks suggested that early blind people were able to develop and apply cognitive understanding of depth cues. Both groups showed generalisation of the learning from the initial phases to cue identification in the maze, and subjectively experienced shapes facing them. Subjects' performance depended not only on their perceptual experience but also on their previous spatial competencies.